ANÁLISIS DEL INVOLUCRAMIENTO Y LA RECONFIGURACIÓN EN YOUTUBE MÉXICO A PARTIR DEL CASO #LADY100PESOS - Dra. Brenda Azucena Muñoz Yáñez (Fonseca, Journal of Communication, 2023)
In this article, I analyze and discuss the acceptance and involvement degree that professional and amateur videos bring forward on YouTube. I take as a starting point the concept of semantic weaveworks (Muñoz, 2014), as an object of study, to explain the ways in which hegemonic and alternative meanings located in these kinds of content intertwine at the act of watching and consuming videos on said platform